Learning organization and organizational commitment in schools - R., Ahmad A.; A, Marinah (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
This paper raised the question of to what extent and how learning organization was accepted, appreciated and practiced at different organizations and its relation to the commitment of the employees. The objective of this study was to identify the relationships between learning organization and organizational commitment among the public primary school principals. A quantitative cross sectional research design with purposive sampling was employed in collecting the data. The questionnaires were based on the Learning Organization and Organizational Commitment indicators that have been modified and used in Malaysia. The respondents for this study were principals of public primary schools who attended the three years intensive program (called the Head-Teacher Degree Program) which would award them the Bachelor’s Degree in Education Management. Two cohorts comprised of 107 principals were chosen from 600 principals who enrolled for the Head-Teacher Degree Program. The study showed that, there was a significant relationship between learning organization and organizational commitment. Therefore, learning organization and organizational commitment are deeply interwoven and opens up new questions to be explored by further research.